Debt management literacy among credit cards users - Alwi, Mohd Afifie bin Mohd; Abdullah, Azwan bin; Luqman, Azyanee binti (Linguistics and Culture Review, 2021)
This research investigates the debt management literacy among credit card users. Based on thematic analysis through semi-structured interviews with debt management experts, particularly in credit cards, this research sheds light on the positive and negative to the causal of debt management literacy, including awareness and experiences. Meanwhile, the negative causal is ignorance and the economy. These themes depict that credit cards users are prone to develop knowledge in debt management for several causes. Taken together, the research findings highlight the importance of understanding the nature of debt management, which has received relatively little attention to date.